Biomechanical specimen assessment by low dose biplanar X-ray study of fusion constructions using a posterior lumbar cage with integrated anchors and posterior adjunctive fixators. Issue 5 (4th April 2022) - Gennari, A.; Langlais, T.; Litrico, S.; Persohn, S.; Allain, J.; Skalli, W.
Abstract: The objective was to compare L4/5 range of motions of fusion constructs using anchored cages. Twelve human cadaveric spine were tested in intact condition, and divided into TLIF and PLIF groups. Testing consisted in applying pure moments in flexion-extension, lateral bending and axial rotation. The computation of intersegmental motion was assessed using 3 D biplanar radiographs. In TLIF group, the addition of contralateral transfacet decreased flexion-extension motion (39%; p = 0.036) but without difference with the ipsilateral pedicle screw construction (53%; p = 0.2). In PLIF group, the addition of interspinous anchor reduced flexion-extension motion (12%; p = 0.036) but without difference with the bilateral pedicle screw construction (17%; p = 0.8).